Feasibility of an exercise-based cardiac rehabilitation algorithm in patients following percutaneous coronary intervention for acute coronary syndrome - Satyamurthy, Akhila; Prabhu, Nivedita; Padmakumar, Ramachandran; Babu, Abraham Samuel (Indian heart journal, 2020)
Cardiac rehabilitation (CR) is underutilised across the world and India. The use of simple algorithms is one way to facilitate CR, however, these algorithms need to be feasible to use across low resource settings. The objectives were to assess the feasibility of a CR algorithm following percutaneous coronary intervention (PCI) for acute coronary syndrome (ACS). A single group, pre-post study on 50 participants undergoing PCI for ACS found significant improvement in various feasibility metrics at discharge and 30-days, with no major adverse events. The proposed CR algorithm was safe and feasible for low and moderate risk patients with ACS undergoing PCI.